Can Treatment for Substance Use Disorder Prescribe the same Substance as that Used? The Case of Injectable Opioid Agonist Treatment - Steel, Daniel (Kennedy Institute of Ethics journal, 2021)
, abstract:, This article examines injectable Opioid Agonist Treatment (iOAT), in which patients suffering from long-term, treatment refractory opioid use disorder (OUD) are prescribed injectable diacetylmorphine, the active ingredient of heroin. While iOAT is part of the continuum of care for OUD in some European countries and in some parts of Canada, it is not an available treatment in the United States. We suggest that one reason for this situation is the belief that a genuine treatment for substance use disorder cannot prescribe the same substance as that used. We examine possible rationales for this belief by considering four combinations of views on the constitutive causal basis of substance use disorders and the definition of effective treatment. We show that all but one combination counts iOAT as a genuine treatment and that there are good reasons to reject the one that does not. Specifically, we claim that medical interventions, such as iOAT, that significantly reduce the severity of a disorder deserve to be categorized as effective treatments and regarded as such in practice.